Внесок двофотонних електронних переходiв у формування активної динамiчної провiдностi трибар’єрних резонансно-тунельних структур iз постiйним електричним полем - Boyko, I. V. (Publishing house "Academperiodika", 2019)
The theory of active dynamic conductivity in a three-barrier resonance tunneling structure subjected to the combined action of a weak electromagnetic field and a longitudinal dc electric field is developed with regard for the contribution of laser-induced one- and two-photon electronic transitions with different frequencies. For this purpose, the full Schr¨odinger equation is solved in the effective mass approximation and with the use of the model of rectangular potential wells and barriers for an electron. The maximum contribution of two-photon transitions to the formation of the total active dynamic conductivity in laser-induced transitions is shown not to exceed 38%. Geometric configurations of the resonance tunneling structure, for which the laser radiation intensity increases due to laser-induced two-photon electronic transitions, are determined.